The Role of Sufis in Connecting Aceh to the Global Islamic Network in the 17th Century - Affan, Muhammad (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2023)
This study explains the roles played by Sufi scholars in building Aceh’s interconnectivity with global Islamic networks in the seventeenth century. It responds to a gap in earlier scholarship, which has often discussed the transmission of Sufi scholars in overly broad terms without specifying the concrete mechanisms through which Aceh was connected to the wider Islamic world. The study employs the historical method, drawing on source-based library research. The analysis focuses on tracing patterns of mobility, scholarly transmission, and correspondence undertaken by Acehnese Sufi scholars during the apex of the Aceh Sultanate. The findings demonstrate that Acehnese Sufi figures such as Hamzah Fansuri, Shaykh ʿAbd al-Raʾūf, and Shams al-Dīn al-Sumatrānī played central roles as agents linking Aceh to international Islamic networks. This connectivity was constructed through intellectual travel, the delegation of students to study in major Middle Eastern centers of Sufism, and correspondence with prominent figures in other parts of the Islamic world. These networks extended from Southeast Asia to North Africa, reinforcing Aceh’s position as a key node in the circulation of knowledge and religious authority. This article contributes to scholarship on the history of Islam in the Malay–Indonesian world and Islamic intellectual networks by offering a more specific mapping of Sufis as transnational actors in shaping Aceh’s relationship with the global Islamic world in the seventeenth century.